Safety and efficacy of double vs. triple antithrombotic therapy in patients with atrial fibrillation with or without acute coronary syndrome undergoing percutaneous coronary interventionï¼š a systematic review and meta-analysis of vitamin k antagonist a - Sophearith, Phav (International Journal of Medicine, 2021)
Objective: To compare the safety and efficacy of double therapy (DT) (no aspirin) versus triple therapy (TT) (with aspirin) antithrombotic drugs in patients with atrial fibrillation and acute coronary syndrome or underwent percutaneous coronary intervention (PCI). Methods: We searched PubMed, Cochrane, Scopus, and Web of Science for relevant articles from inception to December 2020. We conducted the analysis of dichotomous outcomes using risk ratio (RR) and relative 95% confidence interval (CI), while the continuous outcomes were analyzed using mean difference (MD) and relative 95% CI. Heterogeneous outcomes were analyzed with random-effects model, and homogeneous data were analyzed with fixed-effects model. We assessed the risk of bias among the included studies by using Cochraneâ€™s risk of bias tool. Results: A total of five studies were included. Regarding Major or Minor Bleeding, the overall risk ratio was significantly lower with DT group compared with TT group (RR=0.60 [0.45, 0.81], (P = 0.07)). For the safety endpoint (TIMI major or minor bleeding, TIMI major bleeding) favored DT group over TT group, respectively (RR=0.60 [0.45, 0.81], (P = 0.07)); (RR= 0.55 [0.43, 0.70], (P < 0.01)). Intracranial hemorrhage did not differ between both groups (RR=0.62 [0.37, 1.05], (P = 0.07)). The efficacy endpoint, all-cause death showed no significant difference between both groups (RR=1.08 [0.89, 1.31], (P = 0.42)). There were no significant differences between two groups in cardiovascular death, stent thrombosis, myocardial infarction and stroke, respectively (RR=1.10 [0.86, 1.41], (P = 0.43); (RR=1.40 [0.92, 2.12], (P = 0.11); (RR=1.20 [0.98, 1.49], (P = 0.08); (RR=0.95 [0.66, 1.37], (P = 0.79).; respectively). Conclusion: Compared with triple antithrombotic therapy, double antithrombotic therapy is associated with lower bleeding risks, including minor and major bleeding, but the incidence of efficacy endpoints was similar between both groups. Â Â Â